Coexistence of structural and magnetic phases in van der Waals magnet CrI3 - Jaume Meseguer-Sánchez (Nature Portfolio, 2021)
CrI3 is a popular van der Waals magnet that exhibits anomalous magnetic properties between bulk and thin layers due to different crystal symmetry. Here, the authors report the coexistence of different magnetostructural phases over the entire range of temperatures, solving a long-standing puzzle.